Commissioner Independent as Moderation The Relationship of Tax Avoidance and Tax Risk To Firm Value - Oktavianna, Rakhmawati; Benarda, Benarda; Saputri, Sevty Wahiddirani (EAJ (Economic and Accounting Journal), 2024)
The aim of this research is to determine Tax Avoidance And Tax Risk On Firm Value With Independent Commissioners As Moderation in non-cyclical consumer companies listed on the Indonesia Stock Exchange. This research is expected to prove the role of independent commissioners in increasing company value through tax avoidance and tax risk. The type of research used is quantitative research. The population used in this research is 113 non-cyclical consumer companies listed on the Indonesia Stock Exchange from 2018 to 2022. Sample selection used a purposive sampling method and 31 data were selected as research samples. This research uses panel data regression analysis and hypothesis testing. The analytical tool for testing hypotheses by EViews version 10. Based on the results of simultaneous hypothesis testing (f test), tax avoidance and tax risk jointly have a significant effect on firm value and partially (t test), it shows that tax avoidance and tax risk influence firm value. And independent commissioners are able to moderate the relationship between tax avoidance and tax risk on firm value. Keywords: Tax Avoidance, Tax Risk, Company Value, Commissioner Independent